Modification of the Sensory Profile and Volatile Aroma Compounds of Tomato Fruits by the Scion × Rootstock Interactive Effect - Jukić Špika, Maja; Dumičić, Gvozden; Brkić Bubola, Karolina; Soldo, Barbara; Goreta Ban, Smiljana; Vuletin Selak, Gabriela; Ljubenkov, Ivica; Mandušić, Marija; Žanić, Katja (Frontiers in Plant Science, 2021)
Sensory quality is of increasing importance to consumer decisions in choosing a product, and it is certainly an important factor in repurchasing in terms of meeting the necessary aroma quality and taste properties. To better understand the effects of rootstocks and scions on fruit quality, the sensory profile and volatile aroma composition of the fruits of hydroponically grown tomato plants were evaluated. Experiments were established using the tomato cultivars Clarabella and Estatio as scions during two spring-summer seasons. In both experiments, the scion plants were self-grafted or grafted onto rootstocks of cultivars Arnold, Buffon, Emperador, and Maxifort, with the exception that in experiment 1, the Estatio scion was not grafted onto Buffon. The scions and rootstocks caused differences in observed sensory properties in both experiments. For most of the sensory traits, interaction effects between scion and rootstock were observed. Compared to those obtained from self-grafted Clarabella, the fruits obtained from Clarabella grafted onto Buffon in the first experiment and Clarabella grafted onto Arnold in the second experiment were sweeter. The contents of seven aldehydes, six alcohols, five terpenes and two ketones were determined. A lower accumulation of total aldehydes, due to lower amounts of pentanal, (E)-2-heptanal and (E,E)-2,4-decadienal, was found in the fruits from the Arnold and Estatio rootstocks compared with the other rootstocks. Clarabella as a rootstock increased (Z)-3-hexenal + (E)-2-hexenal accumulation. Grafting Clarabella onto the tested rootstocks led to a change in the composition of volatile compounds, while differences between the combinations with Estatio as a scion were generally not recorded. Fruits from self-grafted Clarabella had higher (Z)-3-hexenal + (E)-2-hexenal concentrations than did fruits from Clarabella grafted onto Arnold and Emperador, and in the second experiment, grafting onto all commercial rootstocks reduced (Z)-3-hexenal + (E)-2-hexenal concentrations compared to those from self-grafted Clarabella. Higher (+)-2-carene and (-)-caryophyllene oxide concentrations were attained in plants in which Clarabella was grafted onto Maxifort and plants in which Estatio was grafted onto Arnold compared to self-grafted plants. This study showed the possibility of altering the composition of volatile aroma compounds and sensory properties of tomato fruits by the use of grafting techniques.